Keikutsertaan Anak Anak Dan Perempuan Dalam Perang Menurut Kitab Fathul Qorib - Ahdi, Wafi; Purwono, Andi (Kajian Hubungan Internasional, 2022)
This study aims: To determine the concept of the principles of applicable Islamic law and International Humanitarian Law regarding war; To know the implementation of the principles of applicable Islamic law and International Humanitarian Law regarding War; The scope of this research is the principles of Islamic Law regarding the regulation of war in International Humanitarian Law regarding the involvement of children and women in war; The research method, using a normative juridical approach, is a law-oriented research method that regulates the principles of Islamic law regarding war in International Humanitarian Law. This means collecting primary and secondary data, and tertiary data based on the object of research. The data in question is processed descriptively. The results of the study found that: From a juridical point of view, the Islamic Law System and humanitarian law question the protection of the rights and obligations of the civilian population against the rules regarding how to resolve conflicts and the consequences of the conflict itself. Implementation of the Islamic law system and humanitarian law in regulating legal protection for humans due to armed conflict, namely the existence of fair treatment of fellow human beings as well as respect and protection in the sense that the humanitarian element must be prioritized, so as to prevent acts that excessive as contained in the Geneva Conventions of 1949 and its Additional Protocol to Islamic Law derived from the Qur'an and Al-Hadith. This is meant, broadly speaking, stipulating a prohibition on killing civilians who did not participate in the war, killing children, women and the prohibition of destroying cultural objects, places of worship and other places of benefit.